Training experience is an important factor affecting willingness for bystander CPR and awareness of AED: a survey of residents from a province in Central China in 2023 - Tian, Xueli; Zhang, Yongle; Dou, Dongmei (Frontiers in Public Health, 2024)
Background Bystander cardiopulmonary resuscitation (CPR) and the use of automated external defibrillators (AEDs) may improve survival in patients with out-of-hospital cardiac arrest (OHCA). The purpose of this study was to investigate the effect of CPR training experience and sociodemographic characteristics on bystander CPR willingness and AED awareness. Methods In this study, a questionnaire survey was conducted among 3,569 residents in central China. Descriptive statistics, multiple linear regression and multivariate logistic regression modeling were used to investigate the effect of training experience and sociodemographic characteristics on knowledge of cardiac arrest first aid, awareness of AEDs, and willingness for bystander CPR. Results Of the 3,569 participants, nearly 52% were female, 69.6% were < 23 years old, 23.5% had CPR training and 22.1% had witnessed OHCA. Characteristics of increasing bystander CPR willingness included CPR training experience, male, witnessed OHCA but not acting, knowing whether family members have cardiac disease, older age (>40 years) and lower level of education. Farmers were the subgroup with the least awareness of AED and knowledge of first aid. Conclusion In China, CPR training experience was an important factor in improving bystanders’ CPR willingness, AED awareness and knowledge of cardiac arrest first aid. Additionally, having witnessed OHCA also had a positive effect on bystander CPR willingness.